From the history of education in the Bukey Orda (Journal of history, 2022)
The article analyzes the issues of education development in the Bukei Orda. The authors present a detailed analysis of the general development of education in the region, the history of the emergence of schools and educational institutions, as well as the content of the policy of the tsarist government in the field of education. The article discusses historical facts related to the opening and functioning of schools and educational institutions. Based on archival materials and sources, a large layer of information is presented within the framework of the studied problem. The article provides statistical materials on the number of schools, the contingent of students, the distribution of funds for education, etc. The article analyzes the content of secret circular letters on the translation of Arabic script into Russian graphics, namely such instructions, provisions as the order of the Governor-General of Semipalatinsk region to the GovernorGeneral of the West Siberian region. The authors summarize that the policy of the tsarist government in the field of education was considered as one of the important ways of Russification of colonized peoples. Russian Russian-Kazakh schools The article contains interesting and informative historical material on the work of the first Russian-Kazakh school in the Khan’s headquarters, transformed into a two-grade school, a female one-class school, primary literacy schools, Muslim schools, as well as Russian-Kazakh schools, which were under the jurisdiction of a special inspector of Orda schools. Key words: Bukei Orda, Khan’s headquarters, education, politics, governor-General, circular letter,Russian alphabet, Russian-Kazakh schools.